Diaspora. Transnarodowość – formy funkcjonowania Innego w społeczeństwie wielokulturowym - Rozbicka, Patrycja (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The goal of this article is to characterized the functioning of diasporas and transnationalism which are increasingly difficult to distinguish from each other. Important thesis of submitted paper is the conclusion that the meaning of transnationalism and diaspora must be inferred from their actual uses. Studying individuals in local communities and exploring other cultures doesn‘t require long travels from an anthropologist. ‚Exotic‘ communities left their countries of origin and came to urban centres in search of better future and comfortable space. Representatives of various nationalities, ethnicities, religions and ideas cohabit in European cities today. Metropoles became a melting pot of various cultural identities. Economic migration and immigrant influx is changing the character of European cities and their cultural balance.
Keywords: diaspora; transnationality; multiculturalism; communication; migration; integration